(untitled) (Global Journal of Human-Social Science, 2014)
This research set outs to explore the exact level of the social aspect of integration between Kristang people and their Malay counterparts in Malaysia. It was sure that integration in social aspect is a dilemma which Kristang people face when they interact with Malays as a dominant ethnic group. It suggests that when the process of interaction, their behavior changes in line with the identity of the Malays. This is because the majority influenced the minority in the Malaysian context. Whilst they are welcomed by their Malay counterparts, it is nevertheless hypothesized that they may not assimilate fully into the Malay community.